Economics of Fish Farming in Flood Prone Areas of Bihar with Special Reference to Koshi River System - Planning Commission (Planning Commission, 2009)
Sustainable agricultural development necessitates sustainable aquaculture or sustained production at a level which creates minimal impact on the environment. This is possible only when one carefully applies the economic and ecological principles to aquaculture. Presently most of the world’s fishery resources are near the point of over exploitation it is because of the fact harvesters prefer to avoid under exploitation. Therefore, over exploitation of fish stocks becomes almost unavoidable.
Planning Commission (SER Division)
Planning Commission Government of India